Pelatihan Pengolahan Pakan Asal Limbah Pertanian di Desa Moyo Mekar Moyo Hilir Sumbawa - Muhamad Amin; SD Hasan; Oscar Yanuarianto; Suhubdy Suhubdy; Syamsul Hidayat Dilaga (Universitas Mataram, 2021)
As an effort to improve the knowledge and skills of rural breeders, community service activities have been carried out with the topic